Traditional healers are causing treatment delay among patients with psychosis in Hospital Kuala Lumpur: fact or fallacy? - Phang, Cheng Kar; Midin, Marhani; Abdul Aziz, Salina (ASEAN Federation for Psychiatry and Mental Health, 2010)
Objective: Mental health services in Malaysia often face competition from traditional healers especially among patients with psychosis. The objective of the study is to determine whether patients who sought help earlier from traditional healers had longer duration of untreated psychosis (DUP), and more adverse experiences in pathways to psychiatric care.